PREPATION AND IMPLEMENTATION: MARKETING TOOLS PROGRAM (CASE STUDY AT SUBANG HOSPITAL) - Gugyh Susandy; Mutqi Sopiawadi; Kevin Wahab N; R.Gerry Oktaviandie L; Raphael Rukito Beatus S. (STIESA-PRESS, 2023)
Student service in promoting hospital institutions is an initiative that combines higher education with significant social benefits. Students as agents of social change have a key role in improving the image and quality of hospital services, as well as making real contributions to society and the surrounding environment. This research aims to present a comprehensive picture of student service in promoting hospitals, the methods used, and the resulting impact. The impact of this student service is very significant. First, hospitals gain benefits in the form of improved image and reputation in society, which in turn can increase patient visits and public trust. Furthermore, the community also benefits from student service, such as increased knowledge about health, better access to health information, and support in overcoming certain health problems.